Residual efficacy of deltamethrin and β-cyfluthrin against Trogoderma variabile and Trogoderma inclusum (Coleoptera: Dermestidae). (March 2016) - Ghimire, Mukti N.; Arthur, Frank H.; Myers, Scott W.; Phillips, Thomas W.
Abstract: Trogroderma variabile Ballion, warehouse beetle, and Trogoderma inclusum LeConte, larger cabinet beetle, are dermestid pests of stored products. A series of laboratory bioassays were conducted to evaluate residual toxicity of the pyrethroids deltamethrin and β-cyfluthrin, applied on a concrete surface substrate for control of adults and larvae of both species, to provide initial baseline susceptibility data for dermestids. Commercial formulations were applied at calculated deposition rates of 8, 16, and 24 mg active ingredient [AI] per m 2 for deltamethrin and 10 and 20 mg active ingredient [AI] per m 2 for β-cyfluthrin. Ten adults or larvae of either species were introduced to individual untreated and treated arenas at 0, 0.5, 1, 2, and 3 mo post-treatment. Adult mortality was evaluated after 4 d of exposure with no food provided, and larval mortality was assessed 30 d after exposure with provision of food. Adult mortality of both species exposed to both insecticides ranged from 72.4 ± 6.9 to 100% depending on exposure interval. Larval mortality ranged from 18.3 ± 5.4 to 96.7 ± 2.1% on arenas treated with deltamethrin, and was significantly lower than adult mortality ( P  < 0.001) at bioassays conducted at 2 and 3 mo post-treatment for both species at all three rates. Larval mortality on arenas treated with β-cyfluthrin ranged from 20.0 ± 4.5 to 71.7 ± 4.8%, and was always lower ( P  < 0.001) at all exposure times at both rates for both species. There were only 4 out of a possible 20 comparisons with a significant difference ( P  < 0.05) between the three rates of deltamethrin and no occasions where there is a significant difference in mortality between the two rates of β-cyfluthrin. There were three occasions where mortality of T. inclusum adults or larvae was greater than T. variabile, and one occasion with the reverse, for exposures with deltamethrin. Results show larvae of both species were more tolerant than adults of both species, and larvae could be used as an indicator stage for future studies insecticidal susceptibility of Dermestids. Highlights: The insecticides deltamethrin and β-cyfluthrin provided high levels of control to adults of T. variabile and T. inclusum . Larvae of both species were more tolerant to both insecticides as compared to adults. Deltamethrin provided a higher level of larval mortality than β-cyfluthrin.